Chemically Treated Microwave Biochar From Sago Bark Waste - Rafeah, Wahi; Nur Fakhirah Qurratu'ain, Zuhaidi; Yusralina, Yusof; Jamliah, Jamel; Kanakaraju, Devagi (2018)
Sago bark waste was used to produce biochar via microwave pyrolysis technique. The sample was pyrolyzed in modified household microwave oven in the presence of inert gas for 15 minutes. The biochar obtained was further treated via acid-base modification by using HCl and NaOH. The acid-base treated microwave biochar (M-Bab) were further characterized to identify the physicochemical properties. BET analysis showed improvement in surface morphology and surface are of acid-base treated biochar from microwave biochar. BET analysis showed that the surface area of microwave biochar and acid-base treated biochar were 29.547 m2 /g and 119.040 m2/g, respectively.